2020
DOI: 10.1038/s41598-020-68272-z
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of malaria transmission drivers in Anopheles mosquitoes using artificial intelligence coupled to MALDI-TOF mass spectrometry

Abstract: Vector control programmes are a strategic priority in the fight against malaria. However, vector control interventions require rigorous monitoring. Entomological tools for characterizing malaria transmission drivers are limited and are difficult to establish in the field. To predict Anopheles drivers of malaria transmission, such as mosquito age, blood feeding and Plasmodium infection, we evaluated artificial neural networks (ANNs) coupled to matrix-assisted laser desorption ionization-time of flight (MALDI-TO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 40 publications
0
31
0
Order By: Relevance
“…aegypti , allowing a robust classification according to their infectious status. Similarly, other authors have shown the ability of artificial intelligence to predict Anopheles aging, their blood feeding status and Plasmodium infection when using MALDI-TOF MS spectral profile 25 . These proofs of concept extend the field of applications of MALDI-TOF MS coupled with artificial intelligence in medical entomology.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…aegypti , allowing a robust classification according to their infectious status. Similarly, other authors have shown the ability of artificial intelligence to predict Anopheles aging, their blood feeding status and Plasmodium infection when using MALDI-TOF MS spectral profile 25 . These proofs of concept extend the field of applications of MALDI-TOF MS coupled with artificial intelligence in medical entomology.…”
Section: Discussionmentioning
confidence: 81%
“…Current advances in machine learning approaches could complement and enhance performance of the MALDI-TOF MS to analyze mosquito spectra. For example, it was used to recognize MALDI-TOF MS spectral patterns associated with Anopheles ages, blood-feeding and Plasmodium infection 25 . Machine learning methods is a domain includes all supervise classification methods.…”
Section: Introductionmentioning
confidence: 99%
“…These factors could be promising target for detecting the insecticide resistance through proteomics. In Anopheles mosquitoes, with the help of artificial neural networks (ANNs) and MALDI-TOF/MS, the effect of insecticide resistance on these factors were described [76]. Proteomics detected the contribution of age as one of significant factor to insecticide resistance by using matrix-assisted laser desorption ionization tandem time-of-flight mass spectrometry or capillary high-pressure liquid chromatography with linear ion-trap (LTQ )-Orbitrap XL hybrid mass spectrometer which was further quantified by Western Blot leading to detection of protein biomarkers [77].…”
Section: Proteomics Assaysmentioning
confidence: 99%
“…For instance, Wang et al developed machine-learning models permitting the screening for heterogeneous vancomycin-intermediate Staphylococcus aureus 10 or the recognition of different MLST types of methicillin-resistant Staphylococcus aureus 11 . In a recent study dealing with the use of mass spectra in entomology 12 , Nabet et al . succeeded in extracting information that predicts age, blood-meal status and Plasmodium carriage from female Anopheles MALDI-TOF mass spectra.…”
Section: Introductionmentioning
confidence: 99%